Synthesis of sensitive novel dual Signaling pyridopyrimidine-based fluorescent "turn off" chemosensors for anions determination. (February 2020) - Ashraf, Abida; Khizar, Misbah; Islam, Muhammad; Hameed, Abdul; Tarique Moin, Syed; Yaqub, Muhammad; Rauf, Waqar; Moazzam Naseer, Muhammad; Tayyeb Ahsan, Muhammad; Shafiq, Zahid; Hussain, Javid; Al-Harrasi, Ahmed; et al.
Graphical abstract: Highlights: Synthesis of novel dual Signaling "turn off" Chemosensors for Anions determination. Spectral results showed better sensor detection for F − over acetate and cyanides. The 1 H NMR titrations confirmed the formation of anionic species. This Chemosensors having applications for analysis of F − ion in biological sample. Abstract: The synthesis of 2-hydroxybenzoyl pyridopyrimidines (M1-M4 ) has been carried out with 3-formyl chrome derivatives and 6-amino-1-methyluracil to employ them as anion chemosensors. Pyridopyrimidine-based compounds were studied as colorimetric and fluorescent receptors for anion sensing. The observations with naked eye and the data obtained by UV–visible, fluorescence and 1 H NMR spectroscopy demonstrated selectivity for fluoride, acetate and cyanides among the pool of different anions. However, the spectral data involving fluoride anion showed particularly sharp and strong interactions. In sensing process, the binding of pyridopyrimidine amino (NH) and hydroxyl groups (OH) via hydrogen bonding F − ····H–N/–O induced the colorimetric and "turn off" fluorescent response. The binding mode of action was further studied by 1 H NMR titrations that supported gradual deprotonation mechanism. The fluoride ion detection limit was in the range of 3.51 × 10 −8 M to 1.77 × 10 −6 M for probes M1-M4 and were lower than the maximum permissible concentration of F − ion in drinking water (5.3 × 10 −3 M) set by World Health Organization (WHO) that was found to be influenced by the nature of aromatic substituents. Theoretical study of receptor interactions with fluoride anion via O–H and N–H groups was also carried out at the quantum mechanical level.